Comparative evaluation of the local application of dimethyl sulfoxide in an experimental spinal cord injury model - Ucler, Necati; Kilinc, Suleyman (Annals of Medical Research, 2021)
Aim: To investigate the efficacy of the local application of dimethyl sulfoxide (DMSO) in an experimental spinal cord injury model.Material and Methods: This study included 20 Sprague–Dawley rats (12 males and 8 females) that were aged 4–6 months and weighed 160–300 g. The control and experimental groups had equal number of rats (n = 10). Ketamine hydrochloride (50 mg/kg) and diazepam (2 mg/kg) in saline solution were intraperitoneally administered. A rod bearing, glass tube through which the weight was passed, and modified Allen trauma device were used to induce trauma. The rats then developed post-traumatic flask paraplegia. DMSO was topically applied to the epidural space after a two-level laminectomy. The global motor performance of the rats was evaluated. Results: The motor performance of the experimental and control groups was assessed after trauma. Results showed that the rats presented with significantly decreased motor performance. In particular, the performance of the experimental group improved over time, and recovery accelerated after the fifth day. Based on a histological examination of the lesion sites after the tenth day, the experimental and control groups significantly differed in terms of global motor performance.Conclusion: The efficacy of the agent was evaluated via global motor performance assessment and histological examination. In the experimental group, a statistically significant difference was observed in terms of global motor performance, which was assessed using the tilted floor method, on the fifth day after trauma. Histologically, no statistically significant difference was noted between the two groups.
Keywords: Dimethyl sulfoxide; laminectomy; spinal cord injury